Metabolism of calcidiol and calcium in pregnant and lactating goats - Sakhniuk, V.; Hotsuliak, M.; Melnyk, A.; Marchuk, V.; Samoray, M.; Utechenko, M. (Regulatory Mechanisms in Biosystems, 2025)
The aim of our study was to investigate the dynamics of the metabolism of one of the active metabolites of vitamin D – 25OHD 3 and its effect on the metabolism of total and ionized calcium in pregnant and lactating goats. The subject of the study was Z aanen and L aman goats: pregnant (75–90 and 120–140 days of pregnancy) and lactating animals (0–2 and 15–25 days after ki d ding). The content of 25OHD 3 in the blood serum of goats was in the range of 9.8–54.2 ng/mL, including 10.4–32.4 ng/mL in the pregnant animals (75–140 days) and 9.8–54.2 ng/mL in the lactating animals (0–25 days). The dynamics of calcidiol in the blood serum of the pregnant goats was characterised by a 1.35 - fold increase in its concentration on the 120–140th day s compared to the animals 75–90 days of kidding, with maximum values on the 0–2nd day s after kidding and a decrease in its content on the 15–25th day s of lactation. In clinically healthy goats with optimal serum calcium content, the total concentration of 25OHD 3 ranged from 10.4 to 54.2 ng/mL, including 10.4–32.4 ng/mL in the pregnant animals and 12.1–54.2 ng/mL in the lactating animals. In the su b clinical course of hypocalcaemia, the serum calcidiol content in the blood of goats was in the range of 9.8–29.8 ng/mL, including in pregnant animals – from 11.0 to 21.0 ng/mL, during the first 15–25 th days of lactation – 9.8–29.8 ng/mL. At the optimal content of ionised calcium in the blood serum of goats, the concentration of calcidiol was in the range of 10.4–54.2 ng/mL, against 9.8–29.8 ng/mL in animals with hypocalcaemia. There is a positive correlation between the values of 25OHD3 and total calcium in the blood serum of goats with subclinical hypocalcaemia.